2017
DOI: 10.1097/md.0000000000007129
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary spindle cell carcinoma with unusual morphology

Abstract: Rationale:Pulmonary spindle cell carcinoma (PSCC) is a highly malignant carcinoma that often exhibits the histopathological characteristic of cell pleomorphism.Patient concerns:Here, we report a PSCC case in a 59-year-old woman with multiple metastases. The pathological manifestation of this case did not show high-grade pleomorphism or atypia, and was easily mimicked by other borderline or low-grade malignant tumors such as an inflammatory myofibroblastic tumor (IMT).Diagnoses:Based on the results of immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The prognosis of SpCC is very poor. Only three out of 11 patients had a survival of more than two years in the case series of 11 patients by Qi et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of SpCC is very poor. Only three out of 11 patients had a survival of more than two years in the case series of 11 patients by Qi et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2015 WHO histological classification of lung tumors, pulmonary sarcomatoid carcinoma includes pleomorphic carcinoma, PSCC, giant cell carcinoma, carcinosarcoma, and pulmonary blastoma [1]. Sarcomatoid carcinomas are mostly polymorphic carcinomas, accounting for 0.3 to 1.3% of all lung tumors, especially PSCC [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…After the widespread use of the 2015 WHO histological classification of lung tumors, reports on PSCC have increased. Many reports confirm that cytology alone or endoscopic/percutaneous biopsy is very difficult to prove, as only spindle-shaped tumor cells need to be confirmed for diagnosis, and a definitive diagnosis is rarely obtained before surgery [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the expression of COX-2, [39] as well as the production of ROS and other inflammatory mediators, are induced in RAW 264.7 cells exposed to the bacterial toxin LPS. [40] Moreover, several compounds with antioxidant potential have also been found to be effective against inflammatory diseases and cancer, [40] highlighting oxidative stress as a possible target for developing new antiinflammatory candidates. We examined the ability of 2-oxo-imidazole derivatives 4a-r to reduce ROS production in macrophages activated by LPS.…”
Section: Effects On Ros Production In Lps-activated Raw 2647 Macrophagesmentioning
confidence: 99%